An exploratory survey of long horn beetle damage on the dryland flagship tree species Boswellia papyrifera (Del.) Hochst. (May 2018) - Negussie, Aklilu; Gebrehiwot, Kindeya; Yohannes, Mekonnen; Aynekulu, Ermias; Manjur, Belay; Norgrove, Lindsey
Abstract: Boswellia papyrifera (Del.) Hochst, a flagship tree species in the drylands of Ethiopia, is of high ecological, economic and social value. Recent work has shown that a wood-boring beetle is threatening its survival. In situ and ex situ studies were carried out to study the biology and damage associated with the insect in the dry lowlands of Northern Ethiopia. The beetle's life cycle, biology, and population were studied for 10 months. The mortality of B. papyrifera trees due to the wood-boring beetle was assessed in two land management systems (managed and unmanaged) in 64 (400 m 2 ) randomly allocated plots in Boswellia woodlands of Central and Western Tigray. The beetle was identified as Idactus spinipennis Gahan. Average annual tree mortality attributed to I. spinipennis was up to 7% and 8% ha −1 for Central and Western Tigray, respectively. I. spinipennis has a detrimental effect on the succession of Boswellia woodlands, causing resource loss and fragmentation. Estimated average losses in Central Tigray were 45.7 kg frankincense ha −1 (US $137.1 ha -1 ) and 26.9 kg frankincense ha −1 (US $80.6 ha -1 ) from unmanaged and managed Boswellia woodlands, respectively. Hence immediate management interventions are required to reduce ecological and economic loss of the Boswellia woodland. Highlights: The long horn beetle was Idactus spinipennis Gahan (Cerambycidae). Average annual tree mortality was 7% (central Tigray) 8% (Western Tigray) ha −1 for unmanaged dry Boswellia woodlands. Branch size and number of emerged beetles were positively correlated. Annually the country is losing up to US $137 ha −1 from unmanaged Boswellia woodlands due to loss of frankincense production.